2008
DOI: 10.1002/cncr.23991
|View full text |Cite
|
Sign up to set email alerts
|

Mammary serine protease inhibitor inhibits epithelial growth factor‐induced epithelial‐mesenchymal transition of esophageal carcinoma cells

Abstract: BACKGROUND:By using proteomic technology, the authors previously observed the substantial down‐regulation of mammary serine protease inhibitor (maspin) in esophageal squamous cell carcinoma and metastases. In the current study, they examined the effects of maspin re‐expression in a maspin‐null esophageal cancer cell line EC109 and also investigated the underlying mechanism.METHODS:A cell line with stable maspin expression was established. An epithelial growth factor (EGF)‐induced epithelial‐mesenchymal transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 189 publications
1
15
0
Order By: Relevance
“…5B). In agreement with this, Cia et al (46) have also reported decreased proliferation rates with maspin overexpression in esophageal carcinoma. Also, NAC treatment reversed the oxidative stress phenotype of maspin-deficient or mutant maspin cells, thus indicating that proliferation is a result of increased ROS in these cells.…”
Section: Discussionsupporting
confidence: 72%
“…5B). In agreement with this, Cia et al (46) have also reported decreased proliferation rates with maspin overexpression in esophageal carcinoma. Also, NAC treatment reversed the oxidative stress phenotype of maspin-deficient or mutant maspin cells, thus indicating that proliferation is a result of increased ROS in these cells.…”
Section: Discussionsupporting
confidence: 72%
“…Our study also represents the first report demonstrating the IL6-regulated expression of the E-cadherin, N-cadherin, and vimentin protein in bladder carcinoma cells. A recent study indicated that MASPIN-positive cells were resistant to EGF-induced EMT, suggesting that MASPIN may be involved in the EMT pathways in urothelial-bladder carcinoma [45]. The expression of NDRG1 has been shown to be significantly correlated with the expression of E-cadherin in prostate cancer [46].…”
Section: Discussionmentioning
confidence: 99%
“…SERPINB5 has been associated with prostate cancer, breast cancer (Shao et al, 2008), pancreas cancer (Kashima et al, 2008;Maass et al, 2001) and various types of carcinomas (Bal et al, 2008;Blandamura et al, 2006;Cai et al, 2009 with HCC occurrence, it had a low statistical power (40.8%) and haplotype frequency (0.052), meaning the susceptible population was of a small size and unreliable. Therefore, it is still unsure whether ht5 really had an association with HCC occurrence or was just a false positive association, thus the association may need to be studied again in the future with bigger sample number, preferably with a higher number of subjects that exhibit ht5 haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…However, SERPINB5 is a special case, which acts as a tumor suppressor gene instead of affecting protein pathways. SERPINB5 has previously shown the ability to suppress tumor cells in places such as bones, pancreas, and esophagus (Cai et al, 2009;Hall et al, 2008;Hong et al, 2009). From these findings, it can be inferred that SERPINB5 has a potent ability to suppress tumor cells.…”
Section: Introductionmentioning
confidence: 99%